Differentiation of the Chestnut Tiger Butterfly Parantica sita (Lepidoptera: Nymphalidae: Danainae) in China - Hu, Ping; Lu, Liangzhi; Hu, Shaoji; Da, Wa; Huang, Chia-Lung; Zhang, Huihong; Wang, Di; Zhang, Yifan; Xu, Yongqiang; Wang, Rongjiang (Frontiers in Ecology and Evolution, 2022)
The chestnut tiger butterfly, Parantica sita (Kollar) (Lepidoptera: Nymphalidae: Danainae), occurs in Asia, along the Himalayas, and into the Malayan region. Previous studies found three types of mitogenomes with substantial genetic divergence in samples from China. To clarify the level of differentiation within P. sita, we investigated both molecular data and morphological features in 429 individuals from China. Upon examination, mitochondrial cytochrome oxidase subunit I (COI) sequences showed three substantially diverged haplotype groups. Based on microsatellite genotypes, the samples divided into three clusters that were consistent with the COI haplotype groups. With that genetic data, we named three distinguishable P. sita lineages: PS-A, PS-B, and PS-C. We also found obvious morphological differences in wing color, male sex brand, and genitalia structures among the three lineages. According to the published structure of male genitalia, that of PS-A is identical to that of P. s. sita, and that of PS-B is identical to that of P. pedonga. Based on all the results, we tentatively propose dividing P. sita into three species: PS-A (the former P. s. sita) is the typical Parantica sita (Kollar, [1844]), mainly distributed in southwestern China; PS-C (the former P. s. niphonica) is elevated to full species as Parantica niphonica (Moore, 1883), distributed in Taiwan Island and Japan; and PS-B will be Parantica pedonga Fujioka, 1970, mainly distributed in Tibet and western Sichuan. Divergence time estimates showed that PS-A separated from the PS-B+PS-C clade about 8.79 million years ago (Ma), when the Hengduan Mountains underwent an appreciable elevation increase, isolating the Tibet population from the others. PS-B and PS-C diverged about 4.87 Ma, in accord with the formation of Taiwan Island mountains. The founder effect may explain why PS-C’s genetic diversity is lower than that of the other clades.